Respuesta del cultivo de Rúcula (Eruca vesicaria.), con tres niveles de fertilización, en producción hidropónica, en la zona de Babahoyo, provincia de Los Ríos - Suárez Nieto, César Wladimir (2020)
The present research work was carried out in the Area of Organic Agriculture of the Experimental Farm "San Pablo", Faculty of Agricultural Sciences of the Technical University of Babahoyo. The geographical coordinates of the site are: East: 669 097.17 UTM and North: 9'801 368.24 UTM, with an altitude of 8.05 masl, humid tropical climate, annual temperature of 26.2 oC and rainfall of 1815 mm / year. It also has an annual relative humidity of 76% and 702 hours of annual average heliophany. The objective of the research was to know the response of the arugula (Eruca vesicaria.) Crop, with three levels of fertilization, in hydroponic production, in the Babahoyo area, Los Ríos province. The work carried out is aimed at nitrogen fertilization where the agrocultural practices that are carried out according to the applied system were described. During the work period, it was taken into account that in the table system with substrate the practices are carried out very differently than in the soil, despite having similar characteristics, in solid media we can find inert materials and organic materials maintaining the necessary characteristics such as They are: Retain moisture, good aeration, physical and chemical stability, chemically inert, free of pathogens, good drainage, adequate capillarity, light and low cost. For the fertilization levels, the 46% UREA was used as the only fertilizer in different proportions and arrangements in two different stages of the crop.